Pengasuhan Anak Pasca Perceraian dalam Perspektif Islam - Windiani, Arovah; Samhudi, Gamalel Rifqi; Sodikin (Indra Institute Research & Publication, 2025)
Marriage determines the status of a child, so a child will depend on the marriage between his mother and father. A child who is born into the world will automatically get a man as his father and a woman as his mother, both biologically and legally. The consequences of the divorce have an impact on the child, especially when the child is still in the care of his parents. The problem is how to raise a child if both parent divorce due to a legal or illegal marriage. The research method used is the descriptive-normative method, by explaining, describing, analyzing problems regarding the upbringing of children from divorced parents. The results of the study explain that the consequences of divorce have an impact on children, especially when the child is still in the care of his parents. Islamic law has explained the solution if there is a divorce between the two parents, namely that the child gets his rights such as the right to receive a living and the right to receive inheritance and other custody rights as befits a person who has human rights that must be fulfilled. The applicable law actually provides provisions regarding the upbringing of children due to the divorce of both parents, but Islamic law provides a detailed explanation both regulated in the Qur'an, the Hadith and fiqh. Divorce is meant either because of a legitimate marriage or because of an illegitimate marriage.